2023
DOI: 10.1002/pdi.2435
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities and diabetes

Abstract: Inequalities in health care exist in many countries in the world. In 2008 the then UK Secretary of State for Health commissioned the Marmot review, ‘Fair Society, Healthy Lives’, to propose strategies to address health inequalities in the UK. Most of Marmot's proposals were not acted upon and in 2020, 10 years after the initial recommendations were published, Marmot found that there had been no improvement and some things were worse.In diabetes care inequalities are widespread, impacting on prevention, treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…However, a recent Scottish survey which was designed to gauge local interest in HCL found that interest in acquiring technology was equal across all deprivation quintiles, even though only 6.3% of those from the most deprived socioeconomic quintile were using HCL, compared with 37.4% from the most affluent quintile 37 . Other factors such as age, ethnicity, intellectual disability, may also influence access to technology and clinicians must be alert to these inequalities 38 …”
Section: Selecting People Likely To Benefit From Technology: the Role...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent Scottish survey which was designed to gauge local interest in HCL found that interest in acquiring technology was equal across all deprivation quintiles, even though only 6.3% of those from the most deprived socioeconomic quintile were using HCL, compared with 37.4% from the most affluent quintile 37 . Other factors such as age, ethnicity, intellectual disability, may also influence access to technology and clinicians must be alert to these inequalities 38 …”
Section: Selecting People Likely To Benefit From Technology: the Role...mentioning
confidence: 99%
“…37 Other factors such as age, ethnicity, intellectual disability, may also influence access to technology and clinicians must be alert to these inequalities. 38 While the majority of participants in studies of CSII, CGM and HCL were positive about the technology, studies were usually conducted with a level of technical and clinical support which may be difficult to replicate in routine care. In a study of closed loop insulin delivery during pregnancy, 9/16 women said they would have considered dropping out had they not had 24-hour support during the trial.…”
Section: Selecting People Likely To Benefit From Technology: the Role...mentioning
confidence: 99%